The impact of lateral bow angle variation on an archer`s score - Park, J. L. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2023)
Variation of the bow`s lateral angle (`bow cant` angle) affects the lateral position of arrows on the target, thus impacting an archer`s score. The displacement of arrows on the target depends approximately on the target distance squared and is hence of greatest impact at longer distances. A total of eight archers participated in this study, ranging in skill level from three who have performed at the highest levels internationally through to competent club-level archers, plus the author. The bow cant variation was measured and the impact on archers` scores was calculated, assuming no other score loss mechanisms. The results show that the score loss associated with bow cant angle can be a substantial portion of an archer`s total score loss, particularly for elite archers using recurve bows.